INSTALLATION ON THE PERCEPTION OF MUSICAL WORKS IN THE PROFESSIONAL TRAINING OF A FUTURE MUSIC TEACHER - Musayev Norimbay Usmanovich (Web of Journals Publishing, 2023)
The article discusses the installation on the perception of musical works in the professional training of a future music teacher.
Keywords: music, pedagogy, methodology, piano, pedagogical university.